Impact of CSR Disclosure of the Environmental, Social and Economic on Financial Performance: A Study of Listed Companies in Sri Lanka - Muraleetharan, P. (Jaffna Science Association, 2023)
This study examines whether CSR disclosure of the Environmental, Social and Economic Impact on Financial Performance: A Study of Listed Companies in Sri Lanka. Using a firm-level CSR dataset of listed companies from 2015 to 2021, we estimate OLS models using a fixed-effects and random effects panel estimator. We find that CSR performance is negatively associated with financial performance. Moreover, this positive relationship is stronger for larger firms and firms with stronger market power. We also find that the significant impact of CSR and financial performance. This mutual feedback between the social and financial aspects is key to an ethical business behavior. The board of directors, in following the recommendations of good corporate governance represents the starting point for the application of CSR to business decision-making as it strives to enrich society as a whole.
Keywords: CSR; Environment; Economic; Financial performance and ROA